2013
DOI: 10.1007/s00267-013-0166-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stock Use and Backpackers on Water Quality in Wilderness in Sequoia and Kings Canyon National Parks, USA

David W. Clow,
Harrison Forrester,
Benjamin Miller
et al.

Abstract: During 2010-2011, a study was conducted in Sequoia and Kings Canyon National Parks (SEKI) to evaluate the influence of pack animals (stock) and backpackers on water quality in wilderness lakes and streams. The study had three main components: (1) a synoptic survey of water quality in wilderness areas of the parks, (2) paired water quality sampling above and below several areas with differing types and amounts of visitor use, and (3) intensive monitoring at six sites to document temporal variations in water qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…For example, Tiedemann et al [50] and Gary et al [54] report similar magnitudes of increase in fecal coliform concentrations associated with extensively grazed cattle pastures on Colorado's Front Range and Oregon's Cascade Mountains, respectively. Forrester et al [55] and Clow et al [56] both report comparable values for E. coli in several studies of water quality conditions associated with backpacker and pack livestock trail stream crossings, and near-stream pack stock grazing in national parks in the south Sierra Nevada. Pandey et al [37] found mean E. coli concentrations to be less than 10 cfu/100 mL for sample sites on the mid and upper reaches of the "wild and scenic" designated Merced River Watershed draining Yosemite National Park to the south of the Stanislaus River Watershed, providing some reference for concentrations in limited use watersheds in the region.…”
Section: Fib Concentrations Streamflow Conditions Fecal Sources and S...mentioning
confidence: 89%
“…For example, Tiedemann et al [50] and Gary et al [54] report similar magnitudes of increase in fecal coliform concentrations associated with extensively grazed cattle pastures on Colorado's Front Range and Oregon's Cascade Mountains, respectively. Forrester et al [55] and Clow et al [56] both report comparable values for E. coli in several studies of water quality conditions associated with backpacker and pack livestock trail stream crossings, and near-stream pack stock grazing in national parks in the south Sierra Nevada. Pandey et al [37] found mean E. coli concentrations to be less than 10 cfu/100 mL for sample sites on the mid and upper reaches of the "wild and scenic" designated Merced River Watershed draining Yosemite National Park to the south of the Stanislaus River Watershed, providing some reference for concentrations in limited use watersheds in the region.…”
Section: Fib Concentrations Streamflow Conditions Fecal Sources and S...mentioning
confidence: 89%